Raw Generals and Green Soldiers: Catholic Armies in Ireland From 1641 to 1643. By Pádraig Lenihan. Century of the Soldier 106. Warwick: Helion & Company, 2023. xiv + 173 pp. £ 29.95 paper - Murphy, Elaine (Church history, 2024)
Raw Generals and Green Soldiers: Catholic Armies in Ireland From 1641 to 1643. By Pádraig Lenihan. Century of the Soldier 106. Warwick: Helion & Company, 2023. xiv + 173 pp. £ 29.95 paper. - Volume 93 Issue 3.